Atomic-scale changes of silica-supported catalysts with nanocrystalline or amorphous gallia phases: implications of hydrogen pretreatment on their selectivity for propane dehydrogenation. Issue 12 (11th May 2022) - Castro-Fernández, Pedro; Serykh, Alexander I.; Yakimov, Alexander V.; Prosvirin, Igor P.; Bukhtiyarov, Andrey V.; Abdala, Paula M.; Copéret, Christophe; Fedorov, Alexey; Müller, Christoph R.
Abstract : We explore how H2 pretreatment changes the structure of two gallia-based propane dehydrogenation catalysts, viz. crystalline γ/β-Ga2 O3 and amorphous Ga2 O3 supported on silica, and how it affects their activity, selectivity and stability on stream. Abstract : This work explores how H2 pretreatment at 550 °C induces structural transformation of two gallia-based propane dehydrogenation (PDH) catalysts, viz. nanocrystalline γ/β-Ga2 O3 and amorphous Ga2 O3 (GaO x ) supported on silica (γ-Ga2 O3 /SiO2 and Ga/SiO2, respectively) and how it affects their activity, propene selectivity and stability with time on stream (TOS). Ga/SiO2 –H2 shows poor activity and propene selectivity, no coking and no deactivation with TOS, similar to Ga/SiO2 . In contrast, the high initial activity and propene selectivity of γ-Ga2 O3 /SiO2 –H2 decline with TOS but to a lesser extent than in calcined γ-Ga2 O3 /SiO2 . In addition, γ-Ga2 O3 /SiO2 –H2 cokes less than γ-Ga2 O3 /SiO2 . Ga K-edge X-ray absorption spectroscopy suggests an increased disorder of the nanocrystalline γ/β-Ga2 O3 phases in γ-Ga2 O3 /SiO2 –H2 and the emergence of additional tetrahedral Ga sites (GaIV ). Such GaIV sites are strong Lewis acid sites (LAS) according to studies using adsorbed pyridine and CO probe molecules, i.e., the abundance of strong LAS is higher in γ-Ga2 O3 /SiO2 –H2 compared to γ-Ga2 O3 /SiO2 but lower than in Ga/SiO2 and Ga/SiO2 –H2 . Dissociation of H2 on the Ga–O linkages in γ-Ga2 O3 /SiO2 –H2 yields high-frequency Ga–H bands that are observed in Ga/SiO2 and Ga/SiO2 –H2 but not detected in γ-Ga2 O3 /SiO2 . We attribute the increased amount of GaIV sites in γ-Ga2 O3 /SiO2 –H2 mostly to an increased disorder in γ/β-Ga2 O3 . X-ray photoelectron spectroscopy detects the formation of Ga + and Ga 0 species in both Ga/SiO2 –H2 and γ-Ga2 O3 /SiO2 –H2 . Therefore, it is likely that a minor amount of GaIV sites also forms through the interaction of Ga + (such as Ga2 O) and/or Ga 0 with silanol groups of SiO2 .